Performing Orwell in Progress. (March 2023) - Conti, Norman
This piece was written, memorized, ripped-up, forgotten, improvised, and rewritten in collaboration with returning citizens, police officers, actors, faculty, students, and other chosen family in the Spring semester of 2021. The work was undertaken within an iteration of Roger Guenveur Smith's Phi Beta Kappa course Performing History/Biography in Progress, co-facilitated by Susan Stein, that had been blended with a version of the Inside-Out Prison Exchange Program originally designed for police recruits and incarcerated citizens. Running in a pandemic, during the trial of the former police officer who murdered George Floyd and in the wake of the January 6th insurrection the course became a dialogic exchange in autoethnography where people separated by severe social boundaries could meet in the Zoom platform's electronic box and overcome social distance.